THE ROLE OF HUMAN RESOURCES IN TOURISM DEVELOPMENT TO INCREASE REGIONAL INCOME OF SUMEDANG REGENCY - Ariyanto Ariyanto; Yulianah Yulianah; Joko Ariawan (Jurnal Ekonomi, 2022)
Because the tourist industry is one of the most significant contributors to the overall expansion of a region's economy, it is imperative that all aspects of tourism development be taken into consideration. When it comes to the development of tourism, one factor that needs to be taken into consideration is the issue of human resources. As a result, the purpose of this study is to investigate the function of human resources in the expansion of tourism as a means of boosting the income of the Sumedang district. The approach of qualitative descriptive analysis was utilized in the course of this research. And the data collection instruments include things like observations, document analyses, interviews, and studies of published works of literature. This is how the data is collected. According to the findings of the study, the efforts made by the government of the Sumedang district in order to increase the income of the region include the development of all tourism potentials that are now available. In addition to the role that infrastructure plays in the development of tourism, the role of natural resources also plays an important role; as a result, education and training are required, particularly for human resources, which are primarily the community that is located around tourist attractions